Development of the verbal prefix po- in the Old and Middle Czech - Nejedly, Petr (Bohemica Olomucensia, 2013)
The number of verbs with the prefix po- increases in historical Czech depending on the expanding lexis. Functions of the prefix are changing, e. g. the meaning of a small intensity of a process or its distribution is more frequent in Middle Czech; it is diminishing in the meaning 'the beginning of a process'.